POLA JEJARING KERJASAMA STAKEHOLDER DALAM KETAHANAN SOSIAL DAN EKONOMI DI KAMPUNG AKUAPONIK, KOTA SEMARANG - Nanda Cahyani Putri; Artiningsih Artiningsih (Jurnal Riptek, 2017)
Kampung Akuaponik is one of the new educational tourism destinations in Semarang. Planned and built by internal actors to support Kelurahan Kandri as Tourism Village. The idea of Kampung Akuaponik is derived from cities problem that is influenced by climate change and urbanization, namely Food Security. The development of Kampung Akuaponik is also supported by networking between internal and external stakeholders to build socio-economic resilience. The purpose of this study is to illustrate the pattern of stakeholder cooperation networks in Kampung Akuaponik as a case of community-based adaptation and sustainable environmental management. The qualitative method was applied with an in-depth interview as a data collection technique. Stakeholders analysis was taken to illustrate the role of stakeholders and combined with timeline analysis to recognize the community networks development. There are 2 types of community cooperation network namely personal and institutional pattern. The research findings reveal that the last pattern was dominated on Kampung Akuaponik in Kandri, but the former was give important influenced on the community’s socio-economic resilience.